Managing Imported Fire Ants in Urban Areas - David H. Oi; Philip Koehler (EDIS)
This document provides comprehensive guidelines for managing imported fire ants in urban areas. It covers the identification of fire ant species, the impact of their stings, and various control methods including Integrated Pest Management (IPM) strategies. The article emphasizes the use of both non-chemical and chemical treatments, highlighting the importance of community-wide efforts for effective suppression. It also discusses the USDA quarantine program to prevent the spread of fire ants through regulated articles and offers detailed instructions for treating fire ant infestations in different environments, such as lawns, gardens, and electrical equipment. Original publication date February 1991.